Family forever - George, K. (Kallie), 1983- (George, K. (Kallie), 1983- Heartwood Hotel, 2025)
"As a treasure hunt sets the Fernwood Forest abuzz, Mona the Mouse plans a birthday party at the Heartwood Hotel to bring everyone together"-- Provided by publisher.